2017
DOI: 10.35808/ersj/885
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Banking Adoption in Thailand: An Integration of Technology Acceptance Model and Mobile Service Quality

Abstract: The purpose of this study is to investigate the factors that influence a consumer's intentions to use mobile banking. A web-based survey was employed to collect data from 348 samples of all owners of a mobile device and have experienced with mobile banking applications provide by private banks in Thailand. The proposed model of mobile banking adoption in this study was based on the Technology Acceptance Model (TAM) and Mobile Service Quality (MSQ). Structural equation modeling (SEM) was used to analyze the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
(14 reference statements)
1
18
0
1
Order By: Relevance
“…In a different study, Arcand et al (2017) presented a dimension of service quality measurement in a mobile environment considering utilitarian (Security/Privacy, Practicity) and hedonic values (Design/Aesthetics, Sociality, Enjoyment) based on user experience. Puriwat and Trijopsker (2017) then empirically analyzed the relationship between mobile bank usage intentions using the service quality dimension.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different study, Arcand et al (2017) presented a dimension of service quality measurement in a mobile environment considering utilitarian (Security/Privacy, Practicity) and hedonic values (Design/Aesthetics, Sociality, Enjoyment) based on user experience. Puriwat and Trijopsker (2017) then empirically analyzed the relationship between mobile bank usage intentions using the service quality dimension.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Therefore, this study extracts the measurement attributes of the five dimensions of mobile banking proposed by Arcand et al . (2017) and Puriwat and Trijopsker (2017) to measure the service quality of mobile banking. This two studies have developed and proposed dimensions of service quality of mobile banks based on a questionnaire survey, and this study presents a method of measuring service quality using the mobile bank service quality dimensions proposed by them.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…According to George (2004), any attitude towards the specific or targeted behavior drives the intention of that particular product or service. The construction, source, original items and the adapted questions of attitude towards behavior from (Puriwat & Tripopsakul, 2017).…”
Section: Appendixmentioning
confidence: 99%
“…Subjective norm is powerful to maintain the behavioral intention as the acceptance or the rejection first comes from the society especially in South East Asia. We measured subjective norm by adapting item from (Puriwat & Tripopsakul, 2017) and (Glavee-Geo et al 2017).…”
Section: Appendixmentioning
confidence: 99%
“…Many studies found on the interest using banking technology but very rarely have examined how the adoption after use, the perception of ease and usefulness is a significant way of adopting M-banking. Puriwat and Tripopsakul (2017) uncovered that banks must accentuate procedures to improve the view of the apparent convenience of versatile banking by thinking about these variables. This investigation is likewise one of the first to look at the joined TAM and MSQ model with regards to m-banking appropriation.…”
Section: Research Gapmentioning
confidence: 99%